PEMERIKSAAN PENYAKIT DAN IDENTIFIKASI PARASIT PADA UDANG WINDU (Penaeus monodon) DI TAMBAK TRADISIONAL KABUPATEN PANGKEP - Ilmiah Ilmiah; Amrah Husma; Andi Hamdillah; Ma'ruf Ma'ruf (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
Shrimp farming in Indonesia was initially dominated by Windu Shrimp, but along with the decline in tiger shrimp production due to disease, one of the things that determines the success of shrimp farming businesses, both traditional and intensive, is pest and disease control. Diseases generally occur due to parasitic infections that cause parts of the shrimp's body to be injured, so that other diseases such as fungi, bacteria, and viruses will be more easily exposed to shrimp that have been infected by parasites. This study aims to examine diseases and identify the types of parasites that are cultivated in traditional ponds in Kabba District, Pangkep Regency. There are 15 shrimps with an average size of 14.7 grr and a length of 21.6 cm. This research was carried out in October 2021 - March 2022, the samples were tested at the Integrated Biological Laboratory of the Faculty of Fisheries and Marine Sciences UMI Makassar, South Sulawesi. Ectoparasite examination is carried out on the walking legs, swimming legs and on the tail. The results of the study found 3 (three) types of parasites that infect tiger shrimp, namely Zoothamnium, Vorticella, and Epistylis, all three of which are included in the Ciliata class The prevalence value of the three types of parasites is 50% with the general category (ordinary infection) and an intensity of 41 ind / tail with a moderate category.